The impact of product quality, price, and promotion on the consumer satisfaction of Scarlett Whitening serum products - Afrianti, Windi; Maulana, Arief (Universitas Negeri Padang, 2024)
The purpose of this study was to find out and analyze how product quality, price and promotion have an impact on consumer satisfaction for Scarlett Whitening Serum products among students enrolled in the Faculty of Economics and Business, Padang State University. This research uses quantitative methods. The relationship between two or more variables is investigated in a quantitative study. The population in this study were students of the Faculty of Economics, Padang State University who used scarlett whitening serum products with an unknown amount. Data is collected through an online questionnaire used by Google Forms. The number of samples in this study amounted to 150 using a purposive sampling method. The analysis technique used is SPSS analysis. The results of this study explain that product quality has a significant and positive effect on consumer satisfaction for scarlett whitening serum products for students of the Faculty of Economics and Business, Padang State University. Price has a significant and positive effect on consumer satisfaction for scarlett whitening serum products for students of the Faculty of Economics and Business, Padang State University. Promotion has a significant and positive effect on consumer satisfaction for scarlett whitening serum products for students of the Faculty of Economics and Business, Padang State University.